“Factores psicosociales y el proceso de recaída en pacientes del centro integral de tratamiento de Adiciones Benito Menni, de Quito, periodo abril – septiembre 2016. - Arteaga Cordovez, Natalí Margoth (2017)
This research entitled "Psychosocial factors and the process of relapse in patients Integral Treatment Center of Addictions Benito Menni, Quito, period April to September 2016." had overall objective: To determine the association between psychosocial factors in the relapse process. The sample population included 15 patients who completed the treatment and internment were on an outpatient basis. The research design was non experimental quantitative, based on the inductive method of observation of facts and concludes with the association of psychosocial factors and the relapse process, the type of research was descriptive with cross sectional study. The techniques and instruments used for data collection were: Inventory of risk factors based on 100 ISCA including risk situations and the questionnaire relapse process that values the process. The study showed that variables are associated by 87%, relative to the presence of 7 out of 8 psychosocial factors studied in the process of relapse of patients evaluated due to ineffective coping. The research contributed to the design of a psychological guide relapse prevention, developed based on cognitive behavioral approach by encouraging in treatment related to substance use disorders results, through the proposed strategies is to provide an instrument that improve the quality of life of patients Comprehensive Addiction Treatment Center Benito Menni, Quito.